WAITING LINE ANALYSIS PATENT DRUGS SERVICES IN PHARMACY OUTPATIENT SERVICES - Sujoko, Aris; Chalidyanto, Djazuly (Jurnal Administrasi Kesehatan Indonesia, 2015)
ABSTRACTDuring 2013 until 2014, pharmacy outpatient services had not reached indicator of the standard minimum service. The average time of respons time was over the standard minimum service. It caused complain from patient, in 2014 the highest complain was 83% about time services. The objective of this research was to find better model queueing system to decrease the waiting time. This study is a quantitative descriptive study with cross sectional design and observational method. The sample calculated by proportional random sampling formula, with 74 prescription and collected by accidental random sampling in peak time. Primary data was obtained by observation and secondary data was collected from documentations in pharmacy outpatients service. The highest service time occured in drugs preparation process with 3.71 minutes and the highest waiting time occured in last checking drugs process. The highest utilization rate occurred in drugs preparation process with 256% and after simulation became 73% with increased service rate in 81%. The lowest utilization rate occurred in giving drugs process was 19%. The conclusion from this study was the drugs preparation process had high workload and caused queueing. A suggestion from this research was to add workload for giving drugs process to help drugs preparation process.Â Keywords: outpatient pharmacy, queueing system, simulation